Symbolic Interaction Of Migrant Women In Pontang District, Banten Province - Rahmi Mulyasih; Ahmad Sihabudin; Fahruddin Faiz (Future Science, 2021)
Migrant women are a phenomenon that describes a change in the position of husband and wife in the life of Indonesian society in general. This study aims to explore the interactions that occur between migrant women and their families and communities which then lead to symbols that are interpreted differently by migrant women, families and communities. The research method used in this study uses an ethnomethodological method, which in this research method reflects behavior and tries to understand or interpret someone and others. The results of the study illustrate that there are symbols that are interpreted as meaning the success of migrant women with big and nice houses, jewelry worn and vehicles. These symbols then create a new culture or different interactions between migrant women, both with their families and communities.